Voluntary disclosure of the accounting and auditing organizations for Islamic financial institutions standards by takaful companies - Fahru Azwa Mohd Zain
The current standards of financial reporting, which are based on conventional frameworks, seem insufficient to guide the Islamic fmancial institutions in their preparation of the fmancial reports. Currently, IFls worldwide apply different accounting standards due to the lack of enforcement of international Islamic accounting standards in many countries. This research aims to identify the determinants of the voluntary disclosure of the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) accounting standards and the corporate social responsibility (CSR) disclosure by Islamic insurance (takafu[) companies in tile Southeast Asia (SEA) and Gulf Cooperation Council (GCC) regions. This study examines whether the governance structure and societal variables of takaful companies, have any relationship with the disclosure of the AAOIFI standards. This study uses a sample of 55 takaful companies in the SEA and the GCC regions. Content analysis is used to extract disclosure items from the 2014 annual reports. Agency theory, stakeholder theory and political economy theory are argued to support the voluntary disclosure of the AAOIFI accounting standards and the CSR disclosure of takaful companies. A multiple regression analysis is used to examine the relationships of the variables in the model. The results show that corporate governance (CG) strength has a positive and significant effect on the voluntary disclosure of the AAOIFI accounting standards and CSR disclosure. On the other hand, the level of political right and civil repression has negative and significant effects on both the voluntary disclosure of the AAOIFI accounting standards and the CSR disclosures. In this study, it is found that takaful companies in countries which practice common law disclose more information on CSR than takaful companies in the common law countries. CG plays an important role in the voluntary disclosure of the AAOIFI accounting standards. However, interestingly, Shari 'an Supervisory Board (SSB) as a critical part of Shari 'ah governance system plays a limited role in influencing disclosure in the annual reports of takaful companies. SSB should be able to contribute more by influencing the decisions of the managing board if they follow their suggested role proposed by the Governance Standard for Islamic Financial Institutions (GSIFI) No 2: Shari'ah Review. Additionally, the GSIFI No.3: Internal Shari 'ah Review should also be adopted by takaful companies to harmonise the process of Shari'ah review and opinion.